Hermite-Hadamard and Jensen’s type inequalities for modified (p, h)-convex functions - Feng, Baoli; Ghafoor, Mamoona; Ming Chu, Yu; Imran Qureshi, Muhammad; Feng, Xue; Yao, Chuang; Qiao, Xing (AIMS mathematics, 2020)
In this study, we will derive the conception of modified (p, h)-convex functions which will unify p-convexity with modified h-convexity. We will investigate the fundamental properties of modified (p, h)-convexity. Furthermore, we will derive the Hermite-Hadamard, Fejér and Jensen’s type inequalities for this generalization.